Mediastinal and pericardial hydatidosis: A case report with review of the literature - Insaf Rhalem, MD; Meriem Haloua, MD; Chaymae Hajjar, MD; Nizar El Bouardi, MD; Badreddine Alami, MD; Moulay Youssef Alaoui Lamrani, MD; Mustapha Maaroufi, MD; Meryem Boubbou, MD (Radiology Case Reports, 2023)
Hydatidosis is an echinococcosis caused by the development of Echinococcus granulosus larvae in humans. The lung is the second most frequent site after the liver. The primary mediastinal and pericardial localisations are extremely rare.Ultrasound and CT scans play an important role in the diagnosis of this disease.We report the case of an 11-year-old female patient from a rural environment with a history of dogs contact, whose symptomatology consisted of chest pain, dyspnoea, all evolving in a febrile context. The imagery showed the existence of multiple mediastinal and pericardial collections. This patient was rapidly managed with albendazole (ABZ) and scanography revealed an excellent therapeutic response.Primary mediastinal and pericardial hydatidosis is a very uncommon disease. It can be unfortunately revealed at the stage of vital prognosis complications. Ultrasound and computerized tomography (CT) are helpful for localizing and defining the morphologic features of hydatid cysts. It should be kept in mind, especially in patients from endemic areas.